A Power Loss Ride Through Control Strategy for Variable Speed Drives Based on the Modular Multilevel Matrix Converter - Rojas-Lobos, F; Diaz-Diaz, M; Uriarte-Gonzalez, M; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2021)
Modern variable-speed drives must be able to deal with ride-through faults with dips of 70-90% to ensure the continuity of the process without the energy store station discharge and carry out significant effects to its performance. So, the existent contingencies to such case are tripping-method from grid, robust DC-Link with higher capacitors and additional power electronic hardware. Nevertheless, they comprehend a common drawback for being costly in the industry. Therefore, the Power Loss Ride Through behaviour on variable-speed drives is an important feature which is a worst-case where the system can suffer dips near to 99% on grid. Recently, Modular Multilevel Cascade Converters have been applied in Variable-Speed Drives applications due to their capability to operate at high-power rates and features such as enhanced fault-ride through capability during critical dip voltage (e.g., 99% of amplitude) in grid. Therefore, this paper presents a control strategy based on a transition mechanism between outer control loops on the nested control of a Modular Multilevel Matrix Converter drive with the aim to improve the Power Loss Ride-Through performance through keeping the energy store station uniform and stable. Simulation results obtained using PLECS software are presented to validate the effectiveness of the proposed control strategy. © 2021 IEEE.